Guidelines and Processes for Drug Prevention by Kabang Subdistrict Administrative Organization, Kabang District, Yala Province - วาเด็ง อัฟฟันดี; มะลี รูฟัยดา; วาเย๊ะ อามีเร๊าะ; สุขเสนีย์ คมวิทย์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research article, Guidelines and Processes for Preventing Drug Problems by the Local Administrative Organization of Kabang Subdistrict, Kabang District, Yala Province, aimed to: (1) study the guidelines for drug prevention implemented by the Kabang Subdistrict Administrative Organization, (2) examine the problems and obstacles in the implementation process, and (3) explore recommendations for improving drug prevention in the area. This study employed a qualitative research approach. Data were collected through in-depth interviews with 25 key informants, including one chief executive of the Kabang Subdistrict Administrative Organization, four local administrative officers, one religious leader, eight village heads, eight local residents, and three individuals affected by drug-related problems. A semi-structured interview guide was used as the research instrument, and the data were analyzed using content analysis. The findings revealed that drug prevention guidelines consisted of four main aspects: planning and implementation based on local data and community participation; educational activities to raise awareness about the harmful effects of drugs; continuous public relations and dissemination of drug-related information; and the promotion of alternative activities such as sports and vocational training. The problems and obstacles were identified in three aspects: individual factors, including lack of knowledge and awareness; family factors, including insufficient care and supervision; and social and environmental factors that facilitated access to drugs. The recommendations suggested that drug prevention should be implemented systematically and continuously, with emphasis on rehabilitation and follow-up of former drug users, strengthening cooperation among relevant agencies and communities, and providing adequate budgets and resources to ensure sustainable operations at the local level.